Ventilator Weaning Difficulties in ICU: A Study on VAP Patients with Post-Tracheostomy, Thoracic Trauma, and Thoracic Spinal Cord Injury - Piesesha, Virgiana (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Ventilator weaning failure is an inability to adapt to reduced mechanical ventilator assistance, which can slow down and prolong the weaning process. Ventilator weaning failure is characterized by increased respiratory rate, use of respiratory muscles, gasping breath, out-of-synchronization efforts to assist breathing and ventilator support, shallow breathing, agitation, and abnormal blood gas arteries. Ventilator weaning failure is an inability to spontaneous breathing trial (SBT), re-intubation, and assisted ventilation after extubation or death within 48 hours after extubation. Weaning process failure factors are divided into non-ventilator and ventilator factors. Ventilator factors include poor patient conditions, long-term use of ventilators, and abnormal blood gas analysis (BGA). Meanwhile, the ventilator factor is related to the condition of the patient's lungs that have suffered severe damage or barotrauma and excessive tidal volume pressure. This study analyzes ventilator weaning failure in patients with Ventilator-Associated Pneumonia (VAP), Post Thoracic Trauma, and Post Spinal Cord Injury in Thoracic 10-12 at the intensive care unit. This research method is based on case reports by compiling comprehensive nursing care. The results of the analysis of ventilator weaning failure in this patient are related to the worsening of the patient's condition, complex thoracic trauma, prolonged use of mechanical ventilators causing ventilator-associated pneumonia (VAP), and respiratory acidosis.